EVALUATION OF WORK PRODUCTIVITY AND EMPLOYEE COMPETENCY IN IMPROVING PUBLIC SERVICES AT THE BAROS DISTRICT OFFICE, SUKABUMI CITY - Ardiya Pramadita, Muhamad; Fajar FY Basori, Yana; Purwanti, Dian (Penerbit Lafadz Jaya, 2024)
Employees' work productivity and competence at the Baros District Office, Sukabumi City, must always be evaluated to maximize the public services provided to the community. This study aims to analyze and explain employee competencies and work productivity in improving public services. The research method used is a descriptive method with a qualitative approach. The data collection method was carried out by distributing questionnaires to respondents, namely employees of the Baros District Office, Sukabumi City, which comprised 39 people as a sample in this study. The data analysis technique used is Structural Equation Modeling Partial Least Square (SEM-PLS), which is a statistical analysis used to evaluate the model of linear relationships between variables that cannot be directly observed. The results of the study stated that 1) there was a significant positive influence of employee competence on public services, 2) there was a significant positive influence of employee competence on work productivity, and 3) there was a significant positive influence of work productivity on public services.